Arm Rehabilitation Assistive Device using a Sensory Unit and Arduino (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Rehabilitation of upper limbs is a critical process for individuals recovering from conditions that impair motor functions, such as strokes or injuries. The goal is to restore as much function as possible to the affected limbs, enabling patients to regain independence in their daily activities. This involves a combination of physical therapy, occupational therapy, and sometimes the use of assistive devices or technologies like robotics and virtual reality. Effective rehabilitation is characterized by personalized treatment plans that are developed based on the specific needs and progress of each patient. The success of these programs is often measured by improvements in muscle strength, coordination, range of motion, and the performance of daily tasks . By integrating electromyography (EMG), flex sensors, and accelerometers within an Arduino-based platform, the project embodies a fusion of traditional rehabilitative principles with cutting-edge sensor technology. Methodologically, the project involves the development of customized sensor circuits, data acquisition protocols, and signal processing algorithms to capture intricate physiological nuances related to muscle activity, joint angles, and movement dynamics. Through experimental trials and case studies involving individuals with upper limb impairments, the efficacy and feasibility of the proposed framework are meticulously evaluated. This interdisciplinary endeavor not only contributes to the ongoing evolution of rehabilitation engineering but also underscores the importance of personalized interventions in optimizing patient outcomes and enhancing quality of life.